Preparation of desulfurizing activated carbon from corn stalk and characterization of desulfurizing structure - Li, Fen; Wang, He; Zhang, Yanping; Wang, Qifei (Journal of Environmental Engineering and Landscape Management, 2019)
This study investigated the optimal conditions for preparing desulfurizing stalk carbon, using corn stalk as a raw material and zinc chloride as an activator. The structure of stalk carbon was characterized using thermogravimetry (TG), fourier transform infrared spectroscopy (FT-IR), scanning electron microscopy (SEM), X-ray photoelectron spectroscopy (XPS) and Brunauer – Emmelt – Teller (BET). Results found no significant difference in stalk carbon desulfurization properties when using stalk skin, core, or a skin-core mixture as raw material. The desulfurization performance of stalk carbon prepared using a skin-core mixture, was the most effective when the material : liquid ratio was 1:2; activation temperature was 350 °C; and activation time was 70 min. The corresponding H2S adsorption time was 74 min. The large specific surface area of 562.28 m2/g and abundant pore-volume of 0.3851 ml/g was found in the desulfurization stalk carbon prepared using these conditions. The increase in micropores and the abundant oxygen-containing functional surface groups were conducive to H2S adsorption. The desulfurization products were found to be mainly elemental S and sulfite.